2002
DOI: 10.4049/jimmunol.168.8.3713
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelial Interactions Trigger Specific Regulation of Gene Expression in the M Cell-Containing Follicle-Associated Epithelium of Peyer’s Patches

Abstract: In the intestine, the follicle-associated epithelium (FAE) of Peyer’s patches (PP) performs Ag sampling as the first step in developing immune responses. Depending on the species, this epithelium contains 10–50% of M cells, which act as regulated gates in epithelial barriers that can be used opportunistically by pathogens to invade their host. However, the mechanisms involved in the differentiation and uptake processes of M cells are not known, in part because their limited number in the intestinal mucosa has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Mechanisms of uptake and transport were studied by microscopy and by pharmacological inhibition studies in human FAE tissue, as well as in the in vitro lymphocyte-epithelial cell coculture model of human FAE initially described by Kerneís et al, 11 and subsequently used by several groups to study FAE and M-cell function. [12][13][14][15][16][17][18] Our findings show that human ileal FAE is not only structurally, but also functionally distinct from regular VE, with enhanced transport of antigens and bacteria into the underlying lymphoid tissue.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Mechanisms of uptake and transport were studied by microscopy and by pharmacological inhibition studies in human FAE tissue, as well as in the in vitro lymphocyte-epithelial cell coculture model of human FAE initially described by Kerneís et al, 11 and subsequently used by several groups to study FAE and M-cell function. [12][13][14][15][16][17][18] Our findings show that human ileal FAE is not only structurally, but also functionally distinct from regular VE, with enhanced transport of antigens and bacteria into the underlying lymphoid tissue.…”
mentioning
confidence: 82%
“…In a paper by Kerneís et al 11 it was shown that coculture of Peyer's patch lymphocytes and intestinal epithelial cells may trigger conversion of the epithelial cells to M cells. This model and variants of it have been used to study M-cell function, [12][13][14][15][16][17] and by using our previously established modification 18 of the original model, mechanisms of antigen and bacterial uptake could be studied. Briefly, intestinal epithelial Caco-2 cells were grown on Matrigelt (Becton Dickinson, USA) coated polycarbonate filters (Costar, Baedvenhorp, NL, USA) with a mean pore size of 3.0 mm.…”
Section: Coculture Modelmentioning
confidence: 99%
“…The numbers of M cells vary between species, ranging from percentages as low as 2% of the FAE in humans (15) to an almost homogeneous population in the ruminant ileal Peyer's patch (16,17). The differentiation and uptake processes of M cells are poorly defined (18), mainly because their scarcity in the intestinal mucosa has hampered their cellular and biochemical studies. The existence of M cells outside the FAE capable to sample Salmonella, Yersinia, and gut bacterial Ags has been reported in intestinal villi in mice devoid of Peyer's patches (19).…”
Section: Peyer's Patches M Cells and Dendritic Cells (Dc) 3 In Intementioning
confidence: 99%
“…A more stable model of M-like cells has been obtained by coculturing fully differentiated parental Caco-2 cells (225) or Caco-2 cl1 clone cells (226) with the human Burkitt's lymphoma Raji B cell line. Another model has been constituted from fully differentiated Caco-2 cl1 clone cells cultured in the presence of freshly isolated human blood lymphocytes (227).…”
Section: Coculture Modelsmentioning
confidence: 99%
“…Caco-2 cl1 cells cocultured with mouse PP lymphocytes display much lower levels of SI in their apical membranes than their differentiated Caco-2cl1 counterparts (223); a process that could account for this has been proposed. The conversion of M cell-like cells may be due to the disruption of the brush border resulting from a mouse PP lymphocyte-triggered dedifferentiation process (226). Consistently with this, there was an ϳ2-fold downregulation of the SI promoter in the M cell-like cells compared to Caco-2 cl1 cells, indicating that the lymphoepithelium-induced downregulation of the differentiation-and brush border-associated SI in converted M cell-like cells is the result of a lymphoepithelium-triggered dedifferentiation process of fully differentiated Caco-2 cl1 cells (226).…”
Section: Coculture Modelsmentioning
confidence: 99%